The changing gender gap across the wage distribution in the UK - Bernd Fitzenberger; Gaby Wunderlich (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
This paper contributes descriptive evidence on the development of the gender wage gap for different skill groups and full- and part-time employees in the U.K. The empirical analysis is based upon the General Household Survey from 1975 to 1995 and therefore provides evidence on an exceptionally long period. Our focus is not to provide a causal examination. We rather attempt to identify the macroeconomic trends of wages apart from life cycle and cohort effects implementing a model which takes into account the impact of age, time, and birth cohort simultaneously. Moreover, quantile regression is used to distinguish between various points of the entire wage distribution. We conclude that the wage gap between full-time employed females and full-time employed males has closed considerably during the observation period. The gap has closed mostly in the lower part of the wage distribution. In contrast, part-time employed women did not catch up relative to full-time employed men.
Keywords: J31; J71; J16; 330; Gender Wage Gap; Quantile Regression; Cohort Analysis; Lohndifferenzierung; Geschlecht; Frauenarbeitslohn; Kohortenanalyse; Großbritannien